Placebo Analgesia Does Not Reduce Empathy for Naturalistic Depictions of Others' Pain in a Somatosensory Specific Way. Issue 3 (2nd June 2021) - Hartmann, Helena; Riva, Federica; Rütgen, Markus; Lamm, Claus
Abstract: The shared representations account postulates that sharing another's pain recruits underlying brain functions also engaged during first-hand pain. Critically, direct causal evidence for this was mainly shown for affective pain processing, while the contribution of somatosensory processes to empathy remains controversial. This controversy may be explained, however, by experimental paradigms that did not direct attention towards a specific body part, or that did not employ naturalistic depictions of others' pain. In this preregistered functional magnetic resonance imaging study, we aimed to test whether causal manipulation of first-hand pain affects empathy for naturalistic depictions of pain in a somatosensory-matched manner. Forty-five participants underwent a placebo analgesia induction in their right hand and observed pictures of other people's right and left hands in pain. We found neither behavioral nor neural evidence for somatosensory-specific modulation of pain empathy. However, exploratory analyses revealed a general effect of the placebo on empathy, and higher brain activity in bilateral anterior insula when viewing others' right hands in pain (i.e., corresponding to one's own placebo hand). These results refine our knowledge regarding the neural mechanisms of pain empathy, and imply that the sharing of somatosensory representations seems to play less of a causal role than the one of affective representations.